2005
DOI: 10.1080/10473289.2005.10464612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceiling-Mounted HEPA-UV Air Filters on Airborne Bacteria Concentrations in an Indoor Therapy Pool Building

Abstract: The purpose of this study was to assess the effectiveness of a new generation of high-volume, ceiling-mounted highefficiency particulate air (HEPA)-ultraviolet (UV) air filters (HUVAFs) for their ability to remove or inactivate bacterial aerosol. In an environmentally controlled full-scale laboratory chamber (87 m 3 ), and an indoor therapy pool building, the mitigation ability of air filters was assessed by comparing concentrations of total bacteria, culturable bacteria, and airborne endotoxin with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Cultures obtained from afflicted lifeguards had not been retained, so we were not able to compare directly sequences of the clinical isolates with the pool sequences. The specific enrichment of mycobacteria in the pool air suggested that increased air circulation could reduce the risk of exposure due to inhalation, and, since this investigation, the rate of air exchange in the pool area has been increased (16).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cultures obtained from afflicted lifeguards had not been retained, so we were not able to compare directly sequences of the clinical isolates with the pool sequences. The specific enrichment of mycobacteria in the pool air suggested that increased air circulation could reduce the risk of exposure due to inhalation, and, since this investigation, the rate of air exchange in the pool area has been increased (16).…”
Section: Discussionmentioning
confidence: 71%
“…The volume of the pool water was Ϸ208 m 3 , and the nominal volume of air immediately above the pool was 1,100 m 3 . The air in the pool building was exchanged 48 times daily with outdoor air by the ventilation system (16 sample volume). The air above the pool was sampled by mounting the inlets of the filter and the SAC at Ϸ20 cm above the water surface, taking care to avoid direct splash from entering the samplers.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial cell counts (see Materials and Methods) of typically 1 ϫ 10 4 to 4 ϫ 10 4 cells/m 3 were observed throughout the system (average, 2.2 ϫ 10 4 cells/m 3 ; see Table S1). These directly counted microbial loads were typical of outdoor air samples taken at the same time and at the low end of loads typically encountered in indoor environments such as occupied buildings (10 4 to 10 5 cells/m 3 ) (28)(29)(30). On the other hand, direct counts of aerosolized subway bacteria are much higher, ϳ100-fold higher, than CFU counts encountered in subway environments, which are typically several hundred CFU/m 3 in different subway systems (12)(13)(14).…”
Section: Resultsmentioning
confidence: 86%
“…Most studies focused on UV intensity and exposure time to increase disinfection efficacy (Beggs et al 2006;Chang et al 1985;Chuaybamroong et al 2011;DulebaMajek 2009;Kujundzic et al 2007;Kujundzic et al 2006;Kujundzic et al 2005;Memarzadeh et al 2010;Menzies et al 2003;Rastogi et al 2007;Ryan et al 2010;Tseng and Li 2005;Viscusi et al 2009;Xu et al 2003). pointed out the importance of RH to the performance of UV inactivation.…”
Section: Uv Decontaminationmentioning
confidence: 99%